2016
DOI: 10.1021/acs.chemrev.5b00671
|View full text |Cite
|
Sign up to set email alerts
|

Light-Controlled Radical Polymerization: Mechanisms, Methods, and Applications

Abstract: The use of light to mediate controlled radical polymerization has emerged as a powerful strategy for rational polymer synthesis and advanced materials fabrication. This review provides a comprehensive survey of photocontrolled, living radical polymerizations (photo-CRPs). From the perspective of mechanism, all known photo-CRPs are divided into either (1) intramolecular photochemical processes or (2) photoredox processes. Within these mechanistic regimes, a large number of methods are summarized and further cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
794
2
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,004 publications
(808 citation statements)
references
References 425 publications
5
794
2
7
Order By: Relevance
“…Interestingly,u nlike in an iniferter polymerization, [7] for RAFT polymerization there is no mechanism for the reinitiation of terminated polymer chains following halted chain growth. [18] However,this switchability is commonly observed for analogous photo-initiated RAFT polymerizations. [19] One of the key features of any controlled polymerization is the ability to pre-determine the polymer chain length by adjusting the monomer-to-initiator ratio.W et herefore conducted sonoRAFT with arange of different targeted degrees of polymerization (DP n ), with high monomer conversions obtained (> 75 %) after 60 min and GPC chromatograms that increase with increasing targeted DP n (Figure 3a).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Interestingly,u nlike in an iniferter polymerization, [7] for RAFT polymerization there is no mechanism for the reinitiation of terminated polymer chains following halted chain growth. [18] However,this switchability is commonly observed for analogous photo-initiated RAFT polymerizations. [19] One of the key features of any controlled polymerization is the ability to pre-determine the polymer chain length by adjusting the monomer-to-initiator ratio.W et herefore conducted sonoRAFT with arange of different targeted degrees of polymerization (DP n ), with high monomer conversions obtained (> 75 %) after 60 min and GPC chromatograms that increase with increasing targeted DP n (Figure 3a).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[16,[24][25][26][27][28] As specific examples, considering the activity of PheoA (Figure 1a) and ZnTPP (Figure 1b) with respect to a set of six RAFT agents which comprises dithiobenzoates (4cyanopentanoic acid dithiobenzoate: CPADB, 2-cyano-2-propyl www.advancedsciencenews.com www.advtheorysimul.com Scheme 1. [16,[24][25][26][27][28] As specific examples, considering the activity of PheoA (Figure 1a) and ZnTPP (Figure 1b) with respect to a set of six RAFT agents which comprises dithiobenzoates (4cyanopentanoic acid dithiobenzoate: CPADB, 2-cyano-2-propyl www.advancedsciencenews.com www.advtheorysimul.com Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Recently,t he integration of photo-mediated synthesis with reversible-deactivation radical polymerization (RDRP), including nitroxide-mediated polymerization (NMP), atom-transfer radical polymerization (ATRP), and reversible addition-fragmentation chain-transfer (RAFT) polymerization, is as ignificant advancement in this field. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others.…”
Section: Heteroatom-doped Carbon Dots (Cds) As Ac Lass Of Metal-free mentioning
confidence: 99%
“…

Ak ey challenge of photoregulated living radical polymerization is developing efficient and robust photocatalysts.Now carbon dots (CDs) have been exploited for the first time as metal-free photocatalysts for visible-light-regulated reversible addition-fragmentation chain-transfer (RAFT) polymerization. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others. PET-RAFT polymerization of various monomers with temporal control, narrowdispersity ( % 1.04), and chain-endfidelity was achieved.Besides,itwas demonstrated that the CD-catalyzed PET-RAFT polymerization was effectively performed under natural solar irradiation.

Inspired by the solar-driven biosynthesis of proteins with high chain end fidelity and sequence control, macromolecular research has been focused on the exploitation of light to regulate modern polymer synthesis for ab etter control over the polymerization process.

…”
mentioning
confidence: 99%